Intervenciones de enfermería en paciente de 76 años de edad con hipertensión arterial crónica. - Chinque Sisa, Deicy Gabriela (2020)
High blood pressure is an important disease, since it has a slow progression, it is one of the cardiovascular diseases that obviously affects the quality of life of those who suffer from it. In this clinical case, there is a 76-year-old elderly male patient who has suffered from chronic arterial hypertension for 8 years, for which he receives treatment and control of blood pressure, since this pathology prevents maintaining a proper balance in your lifestyle. During the research carried out in the clinical case, the nursing interventions were analyzed and the main problems that arose during the evolution of the disease were specified, as well as the factors that intervened in the improvement of the patient. Causes of risk that influence the health of the patient were identified, in which an investigation was carried out through bibliographic reviews of different sources, interview, analysis of the clinical history. This has been achieved with the nursing care that the patient must carry out based on the activities of the NIC and NOC. The PAE (Nursing Care Process) is designed to care for patients with hypertension, at the same time helping to improve their health status by monitoring their disease and monitoring their lifestyle, for which it is it must educate the patient in promoting healthy lifestyles.